Sex- and gender-specific medicine: why it's a man's business too - Rubén Fuentes Artiles; Vera Regitz-Zagrosek; Thorsten Buch (Swiss Medical Weekly)
Sex- and gender-specific medicine must expand to include the health disparities affecting men, who face distinct and under-researched health disparities just as women do in some medical fields. Despite its broad relevance, the field is still primarily led by women, which may inadvertently limit male engagement and distort its scope. Men should join women in actively shaping healthcare into a more inclusive and intersectional system that benefits all.